2010
DOI: 10.1111/j.1551-2916.2010.03909.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of TiO2 on the Physicochemical Properties of Cesium Borosilicate Glasses

Abstract: High cesium (Cs)‐bearing sodium borosilicate glasses incorporated with varying concentrations of TiO2 up to 10 mol% at the expense of B2O3 were prepared by the conventional melt quenching method. Physicochemical properties of the glasses studied include Cs volatilization losses, leaching, and glass transition temperatures. Structural aspects of the glasses were investigated using Fourier transform infrared, 11B MAS NMR, and UV‐visible optical absorption techniques. From the detailed investigations on these gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…Such additives generally modify the structure of glass as well as its physicochemical properties like glass transition temperature, thermal expansion coefficient, thermal stability, extent of evaporation of different constituents etc. For example, addition of TiO 2 in sodium borosilicate glass prevents Cs evaporation from Cs containing sodium borosilicate glass [4]. Further, our earlier studies [5] have revealed that addition of BaO in sodium borosilicate glass helps in improving the solubility of sulphate ions containing nuclear waste in the glass.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Such additives generally modify the structure of glass as well as its physicochemical properties like glass transition temperature, thermal expansion coefficient, thermal stability, extent of evaporation of different constituents etc. For example, addition of TiO 2 in sodium borosilicate glass prevents Cs evaporation from Cs containing sodium borosilicate glass [4]. Further, our earlier studies [5] have revealed that addition of BaO in sodium borosilicate glass helps in improving the solubility of sulphate ions containing nuclear waste in the glass.…”
Section: Introductionmentioning
confidence: 96%
“…From this result it is inferred that, even though network modifier concentration is more in BBS glasses compared to NBS glasses, BBS glasses network is thermally more stable compared to NBS glasses. Possible reason for this could be the increased extent of relatively more connected tetrahedral BO 4 -structural units formed at the expense of less connected BO 3 structural units in barium borosilicate glass, brought about by the increased network modifying oxide content. This is also Fig.…”
mentioning
confidence: 95%
“…Other studies used TiO 2 as a network modifier to suppress the volatilisation of Cs from borosilicate glass [19]. However, the later decreased the chemical durability of the waste form.…”
Section: Water Characterisationmentioning
confidence: 98%
“…Titanium is one of the abundant components of oxide glasses and is capable of changing the coordination number from four to six and, depending on its coordination number, acting as a glass-forming or modifying cation in the glass network. The ratio of titanium with different coordination in the glass structure is determined by its chemical composition [1,2] and affects the physical-chemical properties of glasses [3].The aim of the present investigation was to study the effect of titanium additions on the structure of alkali borosilicate glasses acting as the base for glassy matrix materials used for radwaste immobilization. The influence of the composition of these glasses on the coordination of titanium ions and the particularities of the anionic structure of the glass as a whole was studied for the example of titanium-containing borosilicate glasses in the potassium system.…”
mentioning
confidence: 99%
“…Titanium is one of the abundant components of oxide glasses and is capable of changing the coordination number from four to six and, depending on its coordination number, acting as a glass-forming or modifying cation in the glass network. The ratio of titanium with different coordination in the glass structure is determined by its chemical composition [1,2] and affects the physical-chemical properties of glasses [3].…”
mentioning
confidence: 99%